Pedagogical Content Knowledge In Teaching Systems of Linear Equations: A Case of Secondary School Mathematics Teachers - Marhami; Jarnawi Afgani Dahlan; Dadan Dasari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This study aims to examine the Pedagogical Content Knowledge (PCK) of teachers in teaching the Two-Variable Linear Equation System (TVLES) material. A descriptive qualitative approach was employed, involving three mathematics teachers who taught TVLES to eighth-grade junior high school students. Data were collected through semi-structured interviews as well as analysis of instructional portfolios, including lesson plans, worksheets, and teaching materials related to TVLES. The interview protocol consisted of ten questions based on the five components of PCK: orientation to teaching, curriculum knowledge, knowledge of students’ understanding, knowledge of instructional strategies, and knowledge of assessment. The data analysis followed the stages of data collection, reduction, presentation, verification, and conclusion drawing. Data validity was ensured through time triangulation and the use of multiple data sources. The results revealed that teachers demonstrated adequate competency in three PCK component (orientation to teaching, knowledge of students’ understanding, and assessment knowledge), while curriculum knowledge and instructional strategies remained underdeveloped. Based on these findings, it is recommended to establish collaborative forums and provide ongoing mentoring to help teachers enhance their curriculum knowledge and instructional practices. Curriculum developers should also ensure that teachers have sufficient resources and support to implement TVLES materials effectively in the classroom.